PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH FISIKA DENGAN MODEL PEMBELAJARAN INQUIRY-DISCOVERY - Wartono Wartono; John Rafafy Batlolona; Rizqi Maulidina Mahfi (EDUSAINS, 2019)
ENHANCEMENT OF PHYSICS PROBLEM-SOLVING SKILLS WITH INQUIRY-DISCOVERY LEARNING MODEL AbstractThe purpose of this study was to determine differences in problem solving abilities of students who were given inquiry-discovery learning through web-assisted empirical-theoretical reviews with students who were given conventional learning. This study uses a quasi-experimental pretest-posttest control group design. The average gain score of the problem solving ability test shows that students who are taught with inquiry-discovery learning through web-assisted empirical-theoretical reviews are higher than students who are taught with conventional learning. Hypothesis test results show that students who are learning with inquiry-discovery learning through web-assisted empirical-theoretical reviews have higher problem solving abilities than students who are taught with conventional learning, this also applies to students with high or low initial abilities. AbstrakTujuan dari penelitian ini adalah untuk mengetahui perbedaan kemampuan pemecahan masalah siswa yang diberi pembelajaran inquiry-discovery melalui tinjuan empiris-teoritis berbantuan web dengan siswa yang diberi pembelajaran konvensional. Penelitian ini menggunakan rancangan quasi exsperiment pretest-posttest control group design. Hasil rata-rata gain score tes kemampuan pemecahan masalah menunjukkan siswa yang dibelajarkan dengan pembelajaran inquiry-discovery melalui tinjuan empiris-teoritis berbantuan web lebih tinggi daripada siswa yang dibelajarkan dengan pembelajaran konvensional. Hasil uji hipotesis menunjukkan bahwa siswa yang dibelajarakan dengan pembelajaran inquiry-discovery melalui tinjuan empiris-teoritis berbantuan web memiliki peningkatan kemampuan pemecahan masalah lebih tinggi daripada siswa yang dibelajarakan dengan pembelajaran konvensional, hal ini juga berlaku pada siswa yang berkemampuan awal tinggi maupun rendah.